Interaction of clozapine with metformin in a schizophrenia rat model - G. Horvath (Nature Portfolio, 2021)
Abstract The low efficacy of antipsychotic drugs (e.g., clozapine) for negative symptoms and cognitive impairment has led to the introduction of adjuvant therapies. Because previous data suggest the procognitive potential of the antidiabetic drug metformin, this study aimed to assess the effects of chronic clozapine and metformin oral administration (alone and in combination) on locomotor and exploratory activities and cognitive function in a reward-based test in control and a schizophrenia-like animal model (Wisket rats). As impaired dopamine D1 receptor (D1R) function might play a role in the cognitive dysfunctions observed in patients with schizophrenia, the second goal of this study was to determine the brain-region-specific D1R-mediated signaling, ligand binding, and mRNA expression. None of the treatments affected the behavior of the control animals significantly; however, the combination treatment enhanced D1R binding and activation in the cerebral cortex. The Wisket rats exhibited impaired motivation, attention, and cognitive function, as well as a lower level of cortical D1R binding, signaling, and gene expression. Clozapine caused further deterioration of the behavioral parameters, without a significant effect on the D1R system. Metformin blunted the clozapine-induced impairments, and, similarly to that observed in the control animals, increased the functional activity of D1R. This study highlights the beneficial effects of metformin (at the behavioral and cellular levels) in blunting clozapine-induced adverse effects.